Mass transfer in beef: effect of crossbreeding and ultrasound application - Ribeiro Sanches, Marcio Augusto [UNESP]; Onofre Colombo Silva, Patricia Maria [UNESP]; Barbosa, Roger Darros [UNESP]; Romero, Javier Telis [UNESP]; Silva Barretto, Andrea Carla da [UNESP] (Univ Sao Paolo, 2021)
Cuts of muscle (biceps femoris) from three crossbreeds between the Nelore, Angus and Wagyu breeds of cattle (Crossbreed 1 (C1): 1/2 Angus and 1/2 Nelore; Crossbreed 2 (C2): 3/4 Angus and 1/4 Nelore; Crossbreed 3 (C3): 1/2 Wagyu, Nelore and 1/4 Angus) were characterized by their chemical composition, pH, water activity and lipid oxidation. The cuts were submitted to wet brining in a 5 % NaCl concentration at 5 degrees C with either static brine (SB) or brine assisted with ultrasound (US). Samples of the treatments were taken after 30, 60, and 120 min of wet brining for later analysis. The experimental data were adjusted using the Peleg and Page models, and the Page template best described the experimental data. The crossbreeding did not affect the water and ash content; however, it significantly affected the levels of lipids and proteins. C3 presented higher fat content than C2, which, in turn, was higher than C1. C1 had higher protein content than C2, which had more protein than C3. When ultrasound was applied, crossbreeding influenced the water content and the water absorption rate during brining, which had the highest values for the highest protein content. The crossbreeding and ultrasound application also affected the NaCl content of the cuts. However, only ultrasound application increased the rate of NaCl absorption during wet brining. The results demonstrate that ultrasound accelerates the mass transfer in wet brining of the cuts of beef, regardless of the crossbreeds studied.
Keywords: NaCl; Wagyu; Angus; Nelore; water gain